2006
DOI: 10.1007/s11224-006-9063-8
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular architecture of phenylcarbamoylated acetone oxime 1,1-diisopropyl-3-phenylurea] complex

Abstract: Carbamoylated oximes 1 form 1:1 molecular complexes 4 with N,N-dialkyl-N -phenylurea when stirred in THF or ether at room temperature for short time in good yields. The molecular complexes 4a-e were isolated and characterized by analytical and spectral means. X-ray crystallographic analysis for complex 4a was performed. In this paper, we report the use of complex 4a and its moieties as building blocks to form non-interacting polymeric zigzag chains by inter-and intramolecular hydrogen bonds along baxis, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…denote here as ''hydrogen-hydrogen'' (or H-H) bonding [4,5] is one that occurs between similar or identical hydrogen atoms, to be contrasted with the dihydrogen bonding [9][10][11][12][13][14][15][16] between a positively charged hydrogen and a negatively charged hydrogen. The Table in the Appendix contrasts H-H and dihydrogen bonding as the two extremes of a continuum. H-H bonding interactions, as defined above, have been reported in experimental [6,7,[17][18][19][20][21][22][23][24][25][26] theoretical [4,6,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] and chemical informatics [40] studies, both intermolecularly [6, 19, 20, 23-26, 30, 33, 37, 38, 40] and intramolecularly [4, 6, 7, 17, 18, 21, 22, 26-29, 31, 32, 34-36, 39]. The majority of the older literature does not distinguish H-H bonding from dihydrogen bonding, but the closed-shell interaction described in the literature cited above is between similar or identical hydrogens and are, thus, not variants of the hydrogen bond, i.e.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…denote here as ''hydrogen-hydrogen'' (or H-H) bonding [4,5] is one that occurs between similar or identical hydrogen atoms, to be contrasted with the dihydrogen bonding [9][10][11][12][13][14][15][16] between a positively charged hydrogen and a negatively charged hydrogen. The Table in the Appendix contrasts H-H and dihydrogen bonding as the two extremes of a continuum. H-H bonding interactions, as defined above, have been reported in experimental [6,7,[17][18][19][20][21][22][23][24][25][26] theoretical [4,6,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] and chemical informatics [40] studies, both intermolecularly [6, 19, 20, 23-26, 30, 33, 37, 38, 40] and intramolecularly [4, 6, 7, 17, 18, 21, 22, 26-29, 31, 32, 34-36, 39]. The majority of the older literature does not distinguish H-H bonding from dihydrogen bonding, but the closed-shell interaction described in the literature cited above is between similar or identical hydrogens and are, thus, not variants of the hydrogen bond, i.e.…”
Section: Introductionmentioning
confidence: 87%
“…If all close HÁÁÁH contacts were destabilizing, one would not be able to crystallize a hydrocarbon for example. For instance, recent studies have shown how the extensive and complex network of H-H bonding interactions contribute in holding the crystals of 1-phenyl-o-carborane [6] and of acetone oxime-[1,1-diisopropyl-3-phenylurea] complex [7] together. We will review some of the evidence that the presence of close contact often (not necessarily always) results in the appearance of a bond path [8] and in the characteristic hallmarks of closed-shell chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Coşkun et al [235] in the following article report on the use of 1,1-diisopropyl-3-phenylurea complex and its moieties as building blocks to form non-interacting polymeric zigzag chains by inter-and intramolecular hydrogen bonds along b-axis, and details of supramolecular architecture in which there is a intramolecular H-H interaction between hydrogen of a urea NH and neighboring hydrogen of an isopropyl CH linked to an other urea nitrogen. The enthalpy of formation of numerous derivatives of urea have been measured [84,236,237].…”
Section: Issuementioning
confidence: 99%